Respuesta :

First, we are going to add [tex]\frac{1}{2} [/tex] from both sides of the equation: 
[tex]cos(x)tan(x)- \frac{1}{2} + \frac{1}{2} = \frac{1}{2} [/tex]
[tex]cos(x)tan(x)= \frac{1}{2} [/tex]

Next, we are going to use the trig identity: [tex]tan(x)= \frac{sin(x)}{cos(x)} [/tex] to rewrite our expression:
[tex]cos(x)tan(x)= \frac{1}{2} [/tex]
[tex]cos(x) \frac{sin(x)}{cos(x)} = \frac{1}{2} [/tex]
[tex]sin(x)= \frac{1}{2} [/tex]

Finally, using our unitary circle, we can infer that [tex]sin(x)= \frac{1}{2}[/tex] from 0 to [tex]2 \pi [/tex] when [tex]x= \frac{ \pi }{6} [/tex] and [tex]x= \frac{5 \pi }{6} [/tex]

We can conclude that the solutions of the equation cos (x) tan (x) -1/2=0 over the interval [0,2π] are: [tex]x=\frac{ \pi }{6},\frac{5 \pi }{6}[/tex]
Ver imagen cerverusdante